A bibliometric review of scientific theory in futures and foresight: A commentary on Fergnani and Chermack 2021 - Münch, Christopher; Von Der Gracht, Heiko A. (Futures & Foresight Science, 2021)
The important role of scientific theories in social science and across all disciplines has been reflected for decades (see, e.g., Parsons, 1938). With scientific theories, researchers can link the abstract world (the world of concepts/ideas) and the concrete world (the empirical/observable world) (Chibucos et al., 2005). It is, therefore, more than appropriate to question along with Fergnani and Chermack (2021, p. 1) and colleagues, “why the field of futures and foresight has not been successful at becoming part of the social scientific establishment”? Our commentary supports the underlying observations by Fergnani and Chermack (2021) by adopting a brief bibliometric lens on 50 years of cumulative scholarship (1973–January 2021) in 22 selected journals. These 22 journals include a total of 47,049 articles that were scanned. Based on our search criteria, we found 151 article matches (only 0.32 percent), of which a subset of 28 articles applied scientific theories from different disciplines.<br